2013
DOI: 10.12788/j.suponc.0003
|View full text |Cite
|
Sign up to set email alerts
|

Caring for oneself to care for others: physicians and their self-care

Abstract: It is well known that clinicians experience distress and grief in response to their patients' suffering. Oncologists and palliative care specialists are no exception since they commonly experience patient loss and are often affected by unprocessed grief. These emotions can compromise clinicians' personal well-being, since unexamined emotions may lead to burnout, moral distress, compassion fatigue, and poor clinical decisions which adversely affect patient care. One approach to mitigate this harm is self-care, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(186 citation statements)
references
References 62 publications
(59 reference statements)
5
174
2
5
Order By: Relevance
“…In the harried life of a resident, encouraging opportunities to stand back and reflect, even as simple as a text message or a short time-out, gives permission to acknowledge the inherently challenging emotional and humanistic aspects of patient care. These conversations also promote the importance of physician self-care, a prerequisite to one's ability to care for others, 11,45 which may in turn help foster the empathy needed to remain a compassionate physician. A crucial component of fostering open dialogue and awareness of issues surrounding death and dying is establishing palliative carefriendly environments through palliative care and ethics services and consultation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the harried life of a resident, encouraging opportunities to stand back and reflect, even as simple as a text message or a short time-out, gives permission to acknowledge the inherently challenging emotional and humanistic aspects of patient care. These conversations also promote the importance of physician self-care, a prerequisite to one's ability to care for others, 11,45 which may in turn help foster the empathy needed to remain a compassionate physician. A crucial component of fostering open dialogue and awareness of issues surrounding death and dying is establishing palliative carefriendly environments through palliative care and ethics services and consultation.…”
Section: Discussionmentioning
confidence: 99%
“…8 This can have significant negative effects on job satisfaction, psychological and physical wellbeing, and self-image, with consequent burnout and thoughts of quitting. 6,[9][10][11] The vast majority of the literature on moral distress focuses on the nursing profession. 12,13 Several qualitative studies on nurses have demonstrated that moral distress is associated with provision of treatments perceived to be overly aggressive and non-beneficial to patients.…”
Section: Introductionmentioning
confidence: 99%
“…The notion of "self-care," a topic of increasing interest in medical culture [5][6][7], derives from the tendency of physicians to neglect their own health and deny their susceptibility to illness, a tendency driven by a culture that perpetuates the myth of the impervious physician [8,9]. Popular narratives like the 1991 movie The Doctor reflect our culture's struggle with the effects of binary thinking in health care.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining a state of well-being is of paramount importance to healthcare professionals (Sanchez-Reilly et al, 2013). Well-being refers to a state of equilibrium between an individual's coping abilities and the challenges she or he faces (Dodge, Daly, Huyton, & Sanders, 2012).…”
Section: Definitions Of Well-being Stress and Burnoutmentioning
confidence: 99%
“…Given the high levels of stress and mental health concerns in healthcare professionals working in general hospital settings in Singapore, it is reasonable to postulate that healthcare professionals working in mental health settings in Singapore might be experiencing similarly high levels of stress and burnout. If found to be true, this would represent a major concern, as high level of stress and burnout are associated with low job satisfaction, high turnover and decreased patients care (Sanchez-Reilly et al, 2013;; however, it is important to obtain evidence to support this suggestion, in order to inform policy development and appropriate responses.…”
Section: Prevalence Of Stress and Burnout In Mental Health Professionalsmentioning
confidence: 99%